Vibbi - An Interactive Garment Modeling Tool - Freudenthaler, Anton; Thelin, Malin (My University, 2018)
Designing garments is an iterative process which includes pattern creation, draping, and tailoring, which are difficult skills to master. Garments have a 3D shape but are created from patterns which are 2D; this introduces a gap in the design process between prototypes and the finished result. It is believed that this can be shortened in part by visualizing both patterns and the corresponding garment in virtual space. For over 30 years there has been research about digital cloth design [1]. Still, there are few tools in which the user can both model patterns and simulate the corresponding garment in an interactive way. To address this issue we: conducted a literature study in the area of CAD tools for garment design, explored related and available tools on the market, and created Vibbi, an interactive garment modeling tool. With Vibbi, a user can model differently shaped patterns, choose how these patterns should be sewn together, visualize the patterns together in a 3D environment, and finally simulate the patterns as sewn garments. Although Vibbi is not a completely finished product the development of this high fidelity prototype has provided knowledge. Thus, our findings include considerations to take when creating an interactive modeling tool for designing virtual clothes. These considerations can be summarized as: what external tools to use, how to work, how to model patterns, how to sew patterns together, how to dress the avatar, and how to simulate the clothes. While these considerations are not the only ones needed to be taken when creating this type of tool, as they are heavily based on the specific development of Vibbi, we consider them a good start and guide for anyone who is considering creating this type of tool.
Keywords: Data- och informationsvetenskap; Computer and Information Science